-33=-x+7x-3

Simple and best practice solution for -33=-x+7x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33=-x+7x-3 equation:


Simplifying
-33 = -1x + 7x + -3

Reorder the terms:
-33 = -3 + -1x + 7x

Combine like terms: -1x + 7x = 6x
-33 = -3 + 6x

Solving
-33 = -3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-33 + -6x = -3 + 6x + -6x

Combine like terms: 6x + -6x = 0
-33 + -6x = -3 + 0
-33 + -6x = -3

Add '33' to each side of the equation.
-33 + 33 + -6x = -3 + 33

Combine like terms: -33 + 33 = 0
0 + -6x = -3 + 33
-6x = -3 + 33

Combine like terms: -3 + 33 = 30
-6x = 30

Divide each side by '-6'.
x = -5

Simplifying
x = -5

See similar equations:

| h=6t^2+112t+1248 | | -2y^2+16y-x-28=0 | | -2(8t^2-48t-8)=0 | | X^3+4x=80 | | 47.75=5(2.95+x) | | 3(2x+5)-x=-5x-15 | | 3x=27.9 | | 4a^2-7a-2=0 | | x+(4x)=5 | | (2t^2-t-15)/(3t^2-8t-3) | | 3(2x+5)-x=4x+15 | | 6m^2=13m+38 | | =5+7(0)+4 | | ln(x)=1/9 | | y=-4/3x^2-8x | | -3x-23=3x+19 | | 7-4x-6x=-3 | | 2x+(1-x)=7 | | x+(x+1.3)+(x-1.3)=27.9 | | 3(2x+5)-x=15x+5 | | 225=50t | | x-1(x+7)=500 | | 1+4=2+3 | | 6m^2-5m-6=0 | | 3(2x+5)-x=-5x+10 | | y=-3x-23 | | 12-4=3+6 | | 2q+397=813 | | 3(2x+5)-x=-4x+15 | | 19=n+11 | | -8=3+u | | 5a^2-a-18=0 |

Equations solver categories